Highly Sensitive Ammonia Gas Sensors at Room Temperature Based on the Catalytic Mechanism of N, C Coordinated Ni Single-Atom Active Center - Quan, Wenjing; Shi, Jia; Zeng, Min; Lv, Wen; Chen, Xiyu; Fan, Chao; Zhang, Yongwei; Liu, Zhou; Huang, Xiaolu; Yang, Jianhua; Hu, Nantao; Wang, Tao; et al. (Nano-Micro Letters, 2024)
Significant challenges are posed by the limitations of gas sensing mechanisms for trace-level detection of ammonia (NH3). In this study, we propose to exploit single-atom catalytic activation and targeted adsorption properties to achieve highly sensitive and selective NH3 gas detection. Specifically, Ni single-atom active sites based on N, C coordination (Ni–N–C) were interfacially confined on the surface of two-dimensional (2D) MXene nanosheets (Ni–N–C/Ti3C2Tx), and a fully flexible gas sensor (MNPE–Ni–N–C/Ti3C2Tx) was integrated. The sensor demonstrates a remarkable response value to 5 ppm NH3 (27.3%), excellent selectivity for NH3, and a low theoretical detection limit of 12.1 ppb. Simulation analysis by density functional calculation reveals that the Ni single-atom center with N, C coordination exhibits specific targeted adsorption properties for NH3. Additionally, its catalytic activation effect effectively reduces the Gibbs free energy of the sensing elemental reaction, while its electronic structure promotes the spill-over effect of reactive oxygen species at the gas–solid interface. The sensor has a dual-channel sensing mechanism of both chemical and electronic sensitization, which facilitates efficient electron transfer to the 2D MXene conductive network, resulting in the formation of the NH3 gas molecule sensing signal. Furthermore, the passivation of MXene edge defects by a conjugated hydrogen bond network enhances the long-term stability of MXene-based electrodes under high humidity conditions. This work achieves highly sensitive room-temperature NH3 gas detection based on the catalytic mechanism of Ni single-atom active center with N, C coordination, which provides a novel gas sensing mechanism for room-temperature trace gas detection research. Highlights: 1 Exploiting single-atom catalytic activation and targeted adsorption properties, Ni single-atom active sites based on N, C coordination are constructed on the surface of two-dimensional MXene nanosheets (Ni–N–C/Ti3C2Tx), enabling highly sensitive and selective NH3 gas detection. 2 The catalytic activation effect of Ni–N–C/Ti3C2Tx effectively reduces the Gibbs free energy of the sensing elemental reaction, while its electronic structure promotes the spill-over effect of reactive oxygen species at the gas–solid interface. 3 An end-sealing passivation strategy utilizing a conjugated hydrogen bond network of the conductive polymer was employed on MXene-based flexible electrodes, effectively mitigating the oxidative degradation of MXene-based gas sensors.